1999
DOI: 10.1046/j.1464-5491.1999.00104.x
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic fluid insulin levels identify the fetus at risk of neonatal hypoglycaemia

Abstract: Identification of the hyperinsulinaemic fetus before delivery might allow the intensification of maternal insulin therapy leading to a reduction in incidence and severity of diabetic fetopathy. Pregnancy with a normoinsulinaemic fetus could be allowed to continue to the onset of spontaneous labour, which might result in a lower CS rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 15 publications
1
9
0
1
Order By: Relevance
“…Furthermore, there is evidence that neonatal hypoglycemia is much more related to macrosomia per se than to maternal GDM (54). The most important question is: do these metabolic problems really have any permanent negative consequences for the babies' long-term health?…”
mentioning
confidence: 99%
“…Furthermore, there is evidence that neonatal hypoglycemia is much more related to macrosomia per se than to maternal GDM (54). The most important question is: do these metabolic problems really have any permanent negative consequences for the babies' long-term health?…”
mentioning
confidence: 99%
“…Release of P‐IPG in response to insulin has been reported in several cell lines [29] and in normal human term placenta [16]. Hyperinsulinaemia has been reported in fetuses of diabetic mothers [30] with subsequent increased insulin content in the amniotic fluid [31]. Amniotic fluid is enriched with P‐IPG, and the fetus is possibly the source of these molecules [17].…”
Section: Discussionmentioning
confidence: 99%
“…Amniocentesis is considered a reliable intervention to detect fetal hyperinsulinism at the Austrian center (23). Furthermore, several studies have suggested that amniotic fluid insulin levels are a sensitive and representative fetal parameter and a direct measure of fetal metabolic control, independent of placental function (24,25). Amniocentesis in gestational diabetes pregnancies remains uncommon in other centers, as it poses a debatable invasive procedure.…”
Section: Discussionmentioning
confidence: 99%